Arthroplasty - Advanced Techniques and Future Perspectives 2023
DOI: 10.5772/intechopen.109573
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Valgus Knee

Abstract: Total knee arthroplasty in valgus knee deformities continues to be a challenge. It comprises only 10% of patients who undergo total knee arthroplasty. The surgeon should be aware of the technical aspects that differentiate it from the varus deformity: surgical exposure, bone cuts, ligament balancing, gap balancing, joint line obliquity, patellar tracking, preserving fibular nerve function, and selection of the implant. The aim of this chapter is to provide step-by-step comprehensive knowledge about different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…42 Complex deformities including severe valgus with sagittal plane deformities as well as extra-articular deformities lend themselves to planning and correction using robotic systems. 10,26 CAS navigation has been shown to improve certain aspects of the procedure, as shown by Mullaji et al (2010) using navigation to perform lateral femoral epicondylar osteotomy for precise lengthening of the tight lateral structures and to correct TKR alignment in the arthritic knee with extra-articular deformities. 45,46 The routine use of these technologies in addressing the valgus knee deformity has not been widely adopted; however, knowing that they are available and the proposed benefits as well as drawbacks are important for the practicing orthopaedic surgeon.…”
Section: Technology In the Valgus Kneementioning
confidence: 99%
See 2 more Smart Citations
“…42 Complex deformities including severe valgus with sagittal plane deformities as well as extra-articular deformities lend themselves to planning and correction using robotic systems. 10,26 CAS navigation has been shown to improve certain aspects of the procedure, as shown by Mullaji et al (2010) using navigation to perform lateral femoral epicondylar osteotomy for precise lengthening of the tight lateral structures and to correct TKR alignment in the arthritic knee with extra-articular deformities. 45,46 The routine use of these technologies in addressing the valgus knee deformity has not been widely adopted; however, knowing that they are available and the proposed benefits as well as drawbacks are important for the practicing orthopaedic surgeon.…”
Section: Technology In the Valgus Kneementioning
confidence: 99%
“…45,46 The routine use of these technologies in addressing the valgus knee deformity has not been widely adopted; however, knowing that they are available and the proposed benefits as well as drawbacks are important for the practicing orthopaedic surgeon. 4,10 New concepts in classification of knee alignment Hirschmann et al (2019) introduced a novel classification for phenotyping of the coronal alignment of the native knee that highlighted the importance of the orientation of the joint line over and above overall limb alignment. 47 They pointed out limitations in the current system of classifying the overall alignment as either valgus, varus or neutral and suggested that the phenotypic classification would be useful in an individualised TKA approach.…”
Section: Technology In the Valgus Kneementioning
confidence: 99%
See 1 more Smart Citation